Proceedings of the 10th International Conference on Social Media and Society 2019
DOI: 10.1145/3328529.3328562
|View full text |Cite
|
Sign up to set email alerts
|

The Rise of Germany's AfD

Abstract: In 2017, a far-right party entered the German parliament for the first time in over half a century. The Alternative für Deutschland (AfD) became the third largest party in the government. Its campaign focused on Euroscepticism and a nativist stance against immigration. The AfD used all available social media channels to spread this message. This paper seeks to understand the AfD's social media strategy over the last years on the full gamut of social media platforms and to verify the effectiveness of the party'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(13 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…Since 2015, the number of followers has risen significantly, going from 35,000 followers that year (Eskildsen, 2015 ) to 74,000 by September 2016 (Ritzau, 2016 ). Compared to the other Danish parties, DF has by far the most interactions on its Facebook page (Bahn, 2018 ), a finding which is similar to the cases of for example, Alternative for Germany (AfD) and the Sweden Democrats in their domestic settings (Medina Serrano et al., 2019 ; The Local Sweden, 2018 ).…”
Section: Data Setmentioning
confidence: 71%
“…Since 2015, the number of followers has risen significantly, going from 35,000 followers that year (Eskildsen, 2015 ) to 74,000 by September 2016 (Ritzau, 2016 ). Compared to the other Danish parties, DF has by far the most interactions on its Facebook page (Bahn, 2018 ), a finding which is similar to the cases of for example, Alternative for Germany (AfD) and the Sweden Democrats in their domestic settings (Medina Serrano et al., 2019 ; The Local Sweden, 2018 ).…”
Section: Data Setmentioning
confidence: 71%
“…As in 2019, the AfD reached an exceptionally high engagement on Facebook (Serrano et al, 2019), but Die Grünen, instead of the CDU, led the standings of the Facebook advertisement investment in 2021. Nonetheless, they were both overtaken in the overall number of ad impressions by the FDP, who strategically spent less on a higher number of advertisements.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, only the aggregated "other" Prior research points to substantial inter-party differences. Compared to the other six major German parties, the AFD has consistently attracted a much larger and more active audience on Facebook (Serrano, Shahrezaye, Papakyriakopoulos, & Hegelich, 2019;Stier et al, 2018). Magin, Podschuweit, Haßler, and Russmann (2017) found that small parties in Germany and Austria were more inclined to reach out to voters via Facebook.…”
Section: Methodsmentioning
confidence: 99%